User Interface and User Experience (UI/UX) Design for the Ummu Micco Salon Website Using the Design Thinking Approach: Antarmuka Pengguna dan Pengalaman Pengguna (UI/UX) untuk Situs Web Salon Ummu Micco Menggunakan Pendekatan Design Thinking - Fathan Aqsha Ghasani Aufa; Febriyansyah Ramadhan; Debi Irawan (FKOM UNIKU, 2026)
Digital transformation is a strategic solution for Micro, Small, and Medium Enterprises (MSMEs) to maintain global competitiveness, however, its implementation in the beauty service sector is often hindered by operational technology gaps. The primary issue in the Ummu Micco Salon case study is service management inefficiency, which negatively impacts business growth. The underlying cause lies in an inaccessible reservation system and a lack of price transparency, directly resulting in customer confusion and the risk of potential revenue loss. This study aims to address this gap by designing a User Interface (UI) and User Experience (UX) solution built on a website using the Design Thinking approach. The main contribution of this research is implementative, providing a validated design solution that directly resolves the service management inefficiencies faced by the beauty salon. The solution was realized as a high-fidelity prototype using Figma software and validated by 20 respondents. Evaluation results using the System Usability Scale (SUS) measurement indicated a score of 79.625, achieving a Grade B and an